Positron emission tomography‐positive thyroid nodules: rate of malignancy and histological features. Issue 6 (29th August 2014) - Flukes, Stephanie; Lenzo, Nat; Moschilla, Girolamo; Sader, Chady
Abstract: Background: Thyroid nodules may be incidentally detected on 18 F‐FDG‐positron emission tomography (PET) scans. Previous reports suggest a high incidence of malignancy in FDG‐avid nodules. The aims of this study were to examine the incidence of malignancy in a large cohort and to report on the histological features. The findings suggest that poor prognostic histologic features are often associated with FDG‐avid thyroid nodules and this may have clinical implications. Methods: A retrospective review of prospectively collected data was conducted. A database containing all patients who underwent PET scanning at a single tertiary referral centre from January 2006 to January 2013 was searched to identify those with incidental PET‐positive thyroid nodules. Patients with known preexisting thyroid disease were excluded from analysis. The demographics, fine‐needle aspiration (FNA) biopsy result and operative histopathology were analysed. Results: A total of 27 851 FDG‐PET scans were performed of which 221 found incidental PET‐positive thyroid nodules (incidence 0.8%). Fifty‐three patients went on to have further investigation and 21 of these were found to have malignant disease (incidence 39.6%). Histopathological examination of 12 malignant nodules revealed an expected rate of poor prognostic features, including poorly differentiated subtype (8.3%), lymphovascular invasion (16.7%), perineural invasion (8.3%) and extrathyroid extension (33.3%). Conclusion: Our data indicate that PET‐positive thyroid nodules are associated with a high incidence of malignancy. This finding provides strong support for further investigation including FNA biopsy in all surgically suitable patients.